PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MENGGUNAKAN MEDIA WORDWALL UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK SD PADA PELAJARAN MATEMATIKA - Amilia Putri Widyowati; Farida Nursyahidah; Mira Azizah; Diah Saraswati (STKIP Subang, 2023)
Learning Mathematics taught in schools is able to make students have systematic, logical, critical, creative, and consistent thinking. Based on the results of observations, it is known that learning mathematics in class IV A of SDN Sawah Besar 1 has a low level of student activity so that this can affect learning objectives in mathematics. The purpose of this research is to increase the activeness of students in learning mathematics by using the Problem Based Learning learning model and wordwall learning media. This research used a class action research method with 28 research subjects in class IV A at SDN Sawah Besar 1. Data collection techniques used observation and documentation sheets. This research was conducted in two cycles with each cycle consisting of planning, action, observation and reflection. The results showed that the application of the PBL learning model with wordwall media at SDN Sawah Besar 1 class IV A could increase the activeness of students in learning Mathematics. In pre-cycle activities, the activeness of students was only 58.57%, while in cycle I it increased to 67.14%. Where as in cycle II the activity greatly increased to 80%. It can be concluded that the application of the Problem Based Learning learning model with wordwall media can increase the activity of students in learning Mathematics in Elementary School.